Decision Support Systems For Selection Of Pet Cat Using Preference Selection Index (PSI) & Multi-Objective Optimization On The Basis Of Ratio Analysis (MOORA) Methods - Bunga Ayu Ferdiyanti; Yunita Yunita; Nabila Rizky Oktadini (Sriwijaya Journal of Informatics and Applications, 2022)
In its evolution, cats have many variants that make adopters confused in determining the right choice. In the early stages of the search there are several common ways that adopters use, such as visiting websites on the internet, reading magazines or books, or directly coming to a pet store. The search process requires money, effort, and time. Therefore, in this final project was built a Decision Support System for Selection of Pet Cat using Preference Selection Index (PSI) & Multi-Objective Optimization On The Basis Of Ratio Analysis (MOORA) Methods which is expected to be able to help adopters to improve cost efficiency, energy and issued time. This system is expected to be able to provide recommendations for the type of pet cat according to the criteria and needs of the adopter. The criteria used include adoption costs, health, nature, weight, and treatment time. The basic concept of the two method is to calculate the weight of the criteria which is then multiplied by a normalized matrix and ranking. Based on the results of usability testing that applies the Technology Acceptance Model (TAM) theory by distributing questionnaire to 69 respondents, the results obtained are 0.92 with a VERY STRONG relationship level, so this system can be considered useful for users.